Acidification mediated by a river plume and coastal upwelling on a fringing reef at the east coast of Hainan Island, Northern South China Sea. Issue 9 (15th September 2017) - Dong, Xu; Huang, Haining; Zheng, Nan; Pan, Aijun; Wang, Sumin; Huo, Cheng; Zhou, Kaiwen; Lin, Hui; Ji, Weidong
Abstract: We investigated the dynamics of carbonate system which was greatly modulated by a river plume and coastal upwelling in July 2014 and July 2015 at the east coast of Hainan Island where a fringing reef distributes inshore. By using a three end‐member mixing model, we semiquantitatively estimated the removal of dissolved inorganic carbon (DIC) mediated by biological production in the river plume and upwelled water to be 13 ± 17 and 15 ± 16 μmol kg −1, respectively. The enhanced organic production was mainly responsible for these DIC consumptions in both two regimes, however, nearly a half of DIC removal was attributed to biocalcification in the plume system while it was negligible in the upwelling system. Furthermore, the modeled results over reefs revealed that river plume and coastal upwelling were two major threats of acidification to coral communities at the east coast of Hainan Island during cruises. In comparison, the biological contribution to acidification was limited for balancing between organic production and biocalcification during July 2014 cruise, whereas the acidification was greatly intensified by organic degradation during July 2015 cruise. It was verified that naturally local acidification (physical and biological processes) played a major role in great pH decreases on a short‐term scale, leading to coastal waters more vulnerable to anthropogenic "ocean acidification" (uptake of atmospheric CO2 ) by reducing buffering capacity of waters. Finally, effects of acidification associated with other local threats on a fringing reef were further depicted with a conceptual model. Key Points: Biocalcification plays a significant role in regulating carbonate system in the plume system over a fringing reef River plume and coastal upwelling are two major threats of acidification to coastal coral communities A three end‐member mixing model is utilized to diagnose the physical and biological contributions to pH variations over reefs